PEMEROLEHAN BAHASA INDONESIA PAUD ISLAM AL-AMANAH DESA TANJUNG ANOM KECAMATAN GIRIMULYA KABUPATEN BENGKULU UTARA - Dwi Fristika Desmayani; Rokhmat Basuki; Catur Wulandari (Jurnal Korpus, 2018)
The purpose of this research is know the category of vocabulary, phrase, and sentence of Indonesian child of PAUD Islam Al-amanah Tanjung Anom Village, Girimulya District, of North Bengkulu Regency. In this research, it is used descriptive method. Data collection techniques used recordings and field notes. The results showed that children have obtained nine categories of word classes, namely the verb, noun, numeralia, preposition, pronoun, interjection, conjunction, adverb, adjektive. The three categories of phrases are the noun phrase, the verb phrase, and the prepositional phrase. The six categories of sentences are clanged sentences, unpolluted sentences, verb sentences, orderly order sentences, command sentences and news sentences.Keyword: language acquisition, bahasa Indonesia, PAUD